A case of chorea-acanthocytosis with significant improvement of symptoms at one year with deep brain stimulation: case report and literature review - Xu, Yan; Yu, Jiabin; Gao, Yimeng; Su, Qiaozhen; Xie, Haitao; Liang, Hongfeng; Zheng, Chunye (Frontiers in Neurology, 2024)
Chorea-acanthocytosis (ChAc) is a rare, neurodegenerative disorder caused by mutations in the VPS13A gene. In this article, we report on a 32-year-old man diagnosed with ChAc, with involuntary movements of the mouth and trunk, drooling of the mouth, slurred speech, and abnormal vocalizations as the main clinical manifestations. Three weeks after implantation of globus pallidus internal (GPi)-deep brain stimulation (DBS), the patient’s symptoms improved significantly. For example, articulation is clear, involuntary trunk movements and salivation have largely disappeared, and abnormal vocalizations have been significantly reduced. After 1 year of follow-up, the improvement in involuntary movement symptoms is essentially the same as before. As far as we know, we are the first to report the relief of involuntary vocalizations in a patient with GPi-DBS treatment, and that salivation and involuntary trunk movements have almost disappeared, and all other symptoms are significantly relieved, which is rare in previous cases. All of the above proves that the treatment of our case with DBS was very successful and that longer term follow-up is critical. We also hope that our case will provide new references and therapeutic ideas for the future treatment of patients with ChAc.